(untitled) (Research, Society and Development, 2022)
Purpose: To analyze the perception of teachers about the functionality and school participation of children with cerebral palsy (CP). Methods: Descriptive, exploratory, observational study with a mixed design of quantitative and qualitative approach, carried out with 14 teachers, who were interviewed in a questionnaire model, based on the International Classification of Functionality, Disability and Health (ICF). The reports were transcribed and quantified based on the domains and codes of the second level of the ICF, for better analysis. Results: The reports pointed out aspects that facilitate the participatory process of children through the attitudes of the people who make up the school support network. However, the challenges to school inclusion were highlighted, related to issues of recreation, leisure and mobility, restricting participation and environmental barriers, as for services, systems and policies related to construction, architecture, health, and education. Conclusion: Such aspects reinforce the importance of interventions focused on the individuality of the child, taking into account the entire context in which he lives, and not just the intervention limiting the modification of the affected body structures and function. Thus, the teachers interviewed focused on participation in mobility and recreation activities linked to interdisciplinary work, qualification of education professionals, and readjustments in school infrastructure as challenges for greater participation of children with CP.